Recombinant blood group proteins facilitate the detection of alloantibodies to high‐prevalence antigens and reveal underlying antibodies: results of an international study. Issue 7 (18th March 2014) - Seltsam, Axel; Wagner, Franz; Lambert, Mark; Bullock, Tom; Thornton, Nicole; Scharberg, Erwin A.; Grueger, Daniela; Schneeweiss, Clemens; Blasczyk, Rainer
<x xml:space="preserve">Abstract</x> Background Alloantibodies to high‐prevalence red blood cell (RBC) antigens are not easily identified by routine serologic techniques. This multicenter study was conducted to test the effectiveness of recombinant blood group proteins (rBGPs) at regional and international RBC reference laboratories. Study Design and Methods Single or mixed soluble rBGPs (Lu, Yt, Kn, JMH, Sc, Rg, Ch, Do, and Cr) were assessed for their ability to inhibit the reactivity of antibodies to specific antigens. Initially, the effect of rBGPs was validated by testing panels of well‐characterized patient serum samples containing antibodies to high‐prevalence antigens in the hemagglutination inhibition assay. Subsequently, the rBGPs were prospectively used for routine antibody identification and the results were compared to those obtained with RBC‐based diagnostics. Results Panels of predefined antibodies to high‐prevalence antigens were completely and specifically neutralized by the corresponding rBGP specificities. For prospective identification, antibodies to high‐prevalence antigens (n = 62) were specifically inhibited by the corresponding rBGP specificities except for some Complement Receptor 1–related antibodies, which may be directed to epitopes not expressed on the truncated recombinant Kn. In 14 cases, additional clinically relevant alloantibodies were identified. In cross‐matching, the rBGPs were successfully used to inhibit the reactivity of clinically irrelevant antibodies to high‐prevalence antigens to determine compatibility between donor and recipient. Conclusion rBGPs enable the identification of antibodies to high‐prevalence antigens without the need for rare RBC reagents, which are often unavailable. Underlying antibodies can be reliably detected and cross‐matching results validated, resulting in a more efficient blood supply for immunized patients.